1998
DOI: 10.1007/s004240050538
|View full text |Cite
|
Sign up to set email alerts
|

Renal effects of neuropeptide Y

Abstract: Neuropeptide Y (NPY) is a co-transmitter of the sympathetic nervous system including the renal nerves. The kidney expresses NPY receptors, which can also be activated by peptide YY (PYY), a circulating hormone released from gastrointestinal cells. Five subtypes of NPY receptors have been cloned, among which Y1, Y2 and Y5 appear to be involved in the regulation of renal function. NPY produces potent renal vasoconstriction in vitro in isolated interlobar arteries and in the isolated perfused kidney and in vivo u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 94 publications
(202 reference statements)
0
53
1
3
Order By: Relevance
“…In addition to effects in the brain, the NPY system regulates energy homeostasis via actions on Y1 and Y2 receptors in peripheral tissues such as the liver and adipocytes [11,98]. Besides effects on energy balance, the NPY system regulates numerous processes such as fluid balance [99] …”
Section: Neuroendocrine Control Of Bone and Fatmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to effects in the brain, the NPY system regulates energy homeostasis via actions on Y1 and Y2 receptors in peripheral tissues such as the liver and adipocytes [11,98]. Besides effects on energy balance, the NPY system regulates numerous processes such as fluid balance [99] …”
Section: Neuroendocrine Control Of Bone and Fatmentioning
confidence: 99%
“…In addition to effects in the brain, the NPY system regulates energy homeostasis via actions on Y1 and Y2 receptors in peripheral tissues such as the liver and adipocytes [11,98]. Besides effects on energy balance, the NPY system regulates numerous processes such as fluid balance [99] resorption.In addition to estrogen effects on bone, androgens are important regulators of bone cell activity and bone mass in both humans and mice [30]. ARs are found in both osteoblasts and osteoclasts; however, they are primarily expressed in osteoblasts and to a greater degree in cortical than cancellous bone [31].…”
mentioning
confidence: 99%
“…Both in vivo and in vitro studies have demonstrated that NPY inhibits glucose-stimulated insulin secretion (6,7). NPY has also been shown to regulate renal blood flow (8). Stimulation of the NPY receptors in the kidney, using active agonists, may decrease glomerular filtration rate, aldosterone concentration, and plasma renin activity, but increase sodium excretion in the kidney (9).…”
Section: Introductionmentioning
confidence: 99%
“…27 From this NPY receptor distribution, a regulatory role of NPY in renal perfusion and tubular function can be suggested, in accordance with scarce experimental data on the functional renal effects of NPY. 28 Moreover, as we and others provide in vitro evidence for Y1 receptor expression in the precursor cells of RCCs and nephroblastomas, i.e., in tubules and nephrogenic blastema, 27 respectively, it can be assumed that the Y1 receptors in renal tumors are probably not expressed de novo as opposed to the NPY receptors in pheochromocytomas and paragangliomas. 10 Since nephroblastomas express Y1 as well as Y2, one may speculate that a switch in NPY receptor subtype expression occurs in embryonal tumor cells.…”
Section: Discussionmentioning
confidence: 80%
“…While it is possible that binding of NPY to vascular receptors could result in vasoconstriction, 28 tumor ischemia and necrosis, potential direct effects via tumor cell receptors on cell metabolism and proliferation are unclear. It was shown that NPY can inhibit the growth of tumor cell lines under certain conditions 8 and stimulate it in others.…”
Section: Discussionmentioning
confidence: 99%